Late-Onset Neutropenia after Rituximab Treatment for Adult-Onset Nephrotic Syndrome - Mayuko Yamazaki; Hidekazu Sugiura; Yosuke Iwatani; Mizuki Kyoda; Hirohiko Nokiba; Nobuyuki Amemiya; Kosaku Nitta; Ken Tsuchiya (Case Reports in Nephrology)
A 41-year-old woman developed nephrotic syndrome at the age of 32 and was diagnosed with minimal change nephrotic syndrome based on a renal biopsy. Although remission was achieved with administration of prednisolone (PSL) and cyclosporine, the nephrotic syndrome recurred. She was also started on rituximab (RTX). She developed late-onset neutropenia after RTX treatment (R-LON) and improved 17 days later. Although the majority of R-LON cases undergo spontaneous remission, cases of death have been reported. This report is intended to warn about R-LON, since the use of RTX for adult-onset nephrotic syndrome is expected to increase in the future.